2017
DOI: 10.2147/jpr.s132185
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor α modulates sodium-activated potassium channel SLICK in rat dorsal horn neurons via p38 MAPK activation pathway

Abstract: The dorsal horn (DH) of the spinal cord is the integrative center that processes and transmits pain sensation. Abnormal changes in ion channel expression can enhance the excitability of pain-related DH neurons. Sodium-activated potassium (KNa) channels are highly expressed particularly in the central nervous system; however, information about whether rat DH neurons express the SLICK channel protein is lacking, and the direct effects on SLICK in response to inflammation and the potential signaling pathway media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It is known that at the early stage after peritoneal injury, inflammatory responses occur at traumatized sites, in which various proinflammatory factors (e.g., TGF-b1, TNF-a, IL-1b, and IL-6) are released (Zhang et al, 2014). The MAPK inflammation signaling pathway has been reported to be activated by these proinflammatory cascades (Wang et al, 2017). As TGF-b1 and TNF-a were effectively suppressed by CCS (Figs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is known that at the early stage after peritoneal injury, inflammatory responses occur at traumatized sites, in which various proinflammatory factors (e.g., TGF-b1, TNF-a, IL-1b, and IL-6) are released (Zhang et al, 2014). The MAPK inflammation signaling pathway has been reported to be activated by these proinflammatory cascades (Wang et al, 2017). As TGF-b1 and TNF-a were effectively suppressed by CCS (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…10). It has been reported that the activation of the MAPK pathway can also be regulated by IL-1b and IL-6, causing inflammation within injured tissues (Wang et al, 2017). In addition to the MAPK pathway, inflammatory pathways such as Nuclear Factor-k-gene Binding(NF-kB) (Tsai et al, 2013), MEK/ERK (Samarakoon et al, 2005), and Ras homologue protein/Rho associated coiled coil forming protein (Rao et al, 2017) are associated with the formation of intra-abdominal adhesion (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…P38 MAPK, ERK1/2, and JNK pathways are different MAPKs pathway isoforms. When stimulated by different growth factors, cytokines, or pathogens, the MAPKs signaling pathways are activated to participate in the regulation of immune response or inflammatory response by influencing the pathway downstream of multiple cytokines [29][30][31][32]. The MAPK/ERK pathway can also be activated by stressful stimuli and plays an important role in pain development [33].…”
Section: Kyoto Encyclopedia Of Genes and Genomes And Gene Ontology Pa...mentioning
confidence: 99%